2000
DOI: 10.1159/000014436
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Immunological Evaluation of Chronic Hemodialysis in End-Stage Renal Disease Patients

Abstract: Background: Much research has been devoted to the determination of acute leukocyte activation as well as acute cytokines production during and after blood hemodialysis membrane interaction. In contrast, few studies deal with chronic immunological evaluation of T-cell activation markers in hemodialysis. Methods: We evaluated different immune parameters using a modified cellulose low-flux hemophan vs. synthetic high-flux polyamide membrane during 1 year in 35 stable chronic hemodialysis patients. Leukocyte count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…[54][55][56][57][58] Likewise, T lymphocytes from CKD patients show increased expression of early activation markers and heightened apoptotic turnover. [43][44][45][46][47][48][59][60][61] Of note, data from our control patients indicates a progressive state of monocyte activation over the study period. Thus, it seems that the apparent exerciseinduced downregulation of the immune response might be a small price to pay for the anti-inflammatory effects.…”
Section: Effects Of Regular Exercisementioning
confidence: 99%
“…[54][55][56][57][58] Likewise, T lymphocytes from CKD patients show increased expression of early activation markers and heightened apoptotic turnover. [43][44][45][46][47][48][59][60][61] Of note, data from our control patients indicates a progressive state of monocyte activation over the study period. Thus, it seems that the apparent exerciseinduced downregulation of the immune response might be a small price to pay for the anti-inflammatory effects.…”
Section: Effects Of Regular Exercisementioning
confidence: 99%
“…0.450) as suggested by Süsal et al [18], none of the HC but as many as 43% of the ESRF patients showed a high sCD30 serum content. It is reasonable to suggest that a higher serum content of the T cell activation marker sCD30 in ESRF patients might be explained by chronic inflammation and persistent activation of circulating T cells, which are typical phenomena in patients with uremia [30][31][32][33]. This would be in agreement with previous observations in patients with HIV infection or autoimmunity, where in vitro and in vivo findings suggested that acute and chronic inflammatory/ infectious processes stimulate sCD30 secretion, and that high levels of sCD30 in serum and synovial fluid appear to be a reflection of preactivated CD30-committed T cells recruited to inflammatory sites [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in uremic patients, oxLDL seem to play a specific role in the frequencies and phenotypes of CD4 + /CD25 + /CD127¯ Tregs, which distinctly discriminates between nTreg and effector cell subsets [15]. Indeed, in these patients, oxLDL inhibit CD25 expression at the cell surface, whereas the expression of CD3 and CD4 (constitutively expressed on T cells), CD69 (early activation antigen) and HLA-DR (late activation antigen) is unchanged [9,15,41]. Thus oxLDL do not alter the steps of the signalling pathways triggering CD69 and HLADR expression, but mild oxidation of LDL is sufficient to dramatically disturb CD25 expression as demonstrated in a recent study [15].…”
Section: Effects Of Uremia and Oxldl On Cd4 + /Cd25¯ T Cellsmentioning
confidence: 99%
“…Previous findings suggested that in patients with ESKD, a significantly high percentage of activated T cells ultimately did not proliferate but became apoptotic [41,42]. Circulating T cells from HD patients show clear signs of biological activation, likely caused by the combined action of activated complement components, blood-dialyzer interaction, and such dialysate contaminants as endotoxins.…”
Section: Impaired Cd4 + /Foxp3 + Regulatory T Cell Function In Patienmentioning
confidence: 99%